Parental and carer views on the use of AI in imaging for children: a national survey - Girija Agarwal; Raimat Korede Salami; Lauren Lee; Helena Martin; Lahvanya Shantharam; Kate Thomas; Emily Ashworth; Emma Allan; Ka-Wai Yung; Cato Pauling; Deidre Leyden; Owen J. Arthurs; et al. (Insights into Imaging)
Abstract Objectives Although the use of artificial intelligence (AI) in healthcare is increasing, stakeholder engagement remains poor, particularly relating to understanding parent/carer acceptance of AI tools in paediatric imaging. We explore these perceptions and compare them to the opinions of children and young people (CYAP). Materials and methods A UK national online survey was conducted, inviting parents, carers and guardians of children to participate. The survey was “live” from June 2022 to 2023. The survey included questions asking about respondents' views of AI in general, as well as in specific circumstances (e.g. fractures) with respect to children’s healthcare. Results One hundred forty-six parents/carers (mean age = 45; range = 21–80) from all four nations of the UK responded. Most respondents (93/146, 64%) believed that AI would be more accurate at interpreting paediatric musculoskeletal radiographs than healthcare professionals, but had a strong preference for human supervision (66%). Whilst male respondents were more likely to believe that AI would be more accurate (55/72, 76%), they were twice as likely as female parents/carers to believe that AI use could result in their child’s data falling into the wrong hands. Most respondents would like to be asked permission before AI is used for the interpretation of their child’s scans (104/146, 71%). Notably, 79% of parents/carers prioritised accuracy over speed compared to 66% of CYAP. Conclusion Parents/carers feel positively about AI for paediatric imaging but strongly discourage autonomous use. Acknowledging the diverse opinions of the patient population is vital in aiding the successful integration of AI for paediatric imaging. Critical relevance statement Parents/carers demonstrate a preference for AI use with human supervision that prioritises accuracy, transparency and institutional accountability. AI is welcomed as a supportive tool, but not as a substitute for human expertise. Key Points Parents/carers are accepting of AI use, with human supervision. Over half believe AI would replace doctors/nurses looking at bone X-rays within 5 years. Parents/carers are more likely than CYAP to trust AI’s accuracy. Parents/carers are also more sceptical about AI data misuse. Graphical Abstract